INTERNET DAN PEWARTAAN DALAM PESAN PAUS UNTUK HARI KOMUNIKASI SEDUNIA 2002-2016 - Matheus Purwatma (Jurnal Orientasi Baru, 2016)
The Message of the Holy Father John Paul II for 36th the World Communication Day 2002, reflects on the means of the Internet for evangelization,